Bank Competition–Stability Relations in Pakistan: A Comparison between Islamic and Conventional Banks - M. Kabir Hassan; Muhammad Shahzad Ijaz; Mushtaq Hussain Khan (International Journal of Business and Society, 2021)
This study comparatively analyses the financial stability of Islamic and conventional banks in Pakistan. Using data of 29 conventional and 9 Islamic banks over 18 years, the study first estimates bank competition and stability using Lerner index and Z-Score, respectively. Generalized least squares regression is used and the coefficients are estimated by using random-effects estimator. Results of the mean comparison show that Islamic banks carry more market power (less competition) and are more stable compared to their conventional counterparts. Results of a panel regression show that competition positively affects the stability of the banking sector and this effect is higher for Islamic banks due to their market power. Results also show that bank stability in Pakistan was reduced during global crisis period; however, presence of Islamic banks contributes to the stability even during crisis. Finally, this study supports the competition-stability hypothesis for Islamic banking in Pakistan. Recommendations are given at the end.